THE CORRELATION BETWEEN VOCABULARY MASTERY AND WRITING ABILITY - I Gusti Agung Bianca Maharedayadarani Wiguna; I Gusti Agung Putri Wirastuti; Luh Ketut Sri Widhiasih (Academic Journal on English Studies (AJOES), 2021)
The present study which made use of an ex-post facto research with correlation design was intended to figure out the significant between Vocabulary Mastery and Writing Ability of The Eighth-grade Students of SMP N 2 Ubud in Academic Year 2020/2021. The samples of the research consisted of 38 students which were chosen by means of cluster sampling method with lottery system. The data were collected through administering the research instruments which were in the form of structured cloze task and picture description. The obtained data were statistically analyzed by using Pearson product moment correlation and t-test. The results of the data analysis clearly revealed the alternative hypothesis was accepted. In other words, the research findings confirmed that there is significant correlation between Vocabulary Mastery and Writing Ability of the Eighth-grade Students of SMP N 2 Ubud in Academic Year 2020/2021.